THEORETICAL PRESSUPOSITIONS OF EDUCATION: SOME HISTORICAL REFLECTIONS - Rodrigo Regert; Arã Paraguassú Ribeiro; Everaldo da Silva; Joel Haroldo Baade (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
Education has always been a much discussed theme and continues to be so. Based on this idea, the goal of this article is to discuss the theoretical pressupositions of education, beginning with the idea itself of human intellectual development and passing through the Ancient, Medieval, Modern and Contemporary Ages. It is important to point out that the article does not have the intention of covering the whole of this theme, nor even all of the theoretical pressupositions, which would be impossible. But it intends to begin or at least continue this discussion. For this the research made use of the descriptive method and its technical procedures took place in a bibliographic way. We conclude that it is important to discuss the theoretical pressupositions of education in history since, without this, it is not even possible to understand current education.